2007
DOI: 10.1111/j.1474-9726.2007.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of being subtle: small changes in calcium homeostasis control cognitive decline in normal aging

Abstract: SummaryAging is a complex, multifactorial process. One of the features of normal aging of the brain is a decline in cognitive functions and much experimental attention has been devoted to understanding this process. Evidence accumulated in the last decade indicates that such functional changes are not due to gross morphological alterations, but to subtle functional modification of synaptic connectivity and intracellular signalling and metabolism. Such synaptic modifications are compatible with a normal level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(132 citation statements)
references
References 108 publications
0
132
0
Order By: Relevance
“…The age-related changes in neuronal Ca 2+ signalling have been well established [88][89][90]. It has been shown that Ca 2+ release from intracellular stores is increased in the aging neurons, similar to neurons that express PS1-FAD mutants with loss of ER Ca 2+ leak leak function.…”
Section: Neuronal Ca 2+ Signalling and Sporadic Admentioning
confidence: 96%
“…The age-related changes in neuronal Ca 2+ signalling have been well established [88][89][90]. It has been shown that Ca 2+ release from intracellular stores is increased in the aging neurons, similar to neurons that express PS1-FAD mutants with loss of ER Ca 2+ leak leak function.…”
Section: Neuronal Ca 2+ Signalling and Sporadic Admentioning
confidence: 96%
“…Indeed subtle declines in mechanisms that modulate [Ca 2+ ]i levels may be responsible for the elevated resting cytosolic [Ca 2+ ]i that has been seen in several types of peripheral and central neurons in tissue culture, as well as in acutely isolated tissue slices or neurons (Kirischuk & Verkhratsky, 1996;Verkhratsky & Toescu, 1998;Raza et al, 2007). One potential consequence of an age-related decline in regulation of intracellular calcium is that calcium overload increases mitochondrial calcium uptake, in turn activating caspases that mediate neuronal cell apoptosis, reducing neuronal survival with age (Ichas & Mazat, 1998;Thibault et al ., 1998;Begley et al ., 1999;Toescu, and Verkhratsky, 2007).…”
Section: General Overview Of Calcium Regulation In Aging Neuronsmentioning
confidence: 99%
“…Cell death is not restricted to one cell, but intercellular junctions mediate spreading of cell death to neighboring cells, a mechanism that could be very important in targeting cancer cells as is further discussed in a contribution by L. Leybaert and colleagues [60,61]. Exaggerated or inappropriate cell death consistently leads to severe pathologies including particularly neurodegenerative diseases [62] and normal aging [63,64]. Anomalous neuronal Ca 2+ signaling and its consequences for neuronal cell death is discussed by C. Supnet and I. Bezprozvanny in this Special Issue.…”
Section: Camentioning
confidence: 99%